A Review of International Best Practice in Sustainable Airport Management - Lo, Yee Wen (Curtin University, 2017)
The main objective of this research is to provide recommendations regarding best sustainability management practices at airports. An operational flowchart of targeted sources of carbon emissions at international airports provides an understanding of the scale, source and scope of emissions in airport sustainability management. A survey was conducted to review international airports sustainability practices with airport managers. The outcome of this study provides recommendations regarding the best practice in sustainability management practices at airports.